Debating women, politics, and power in early modern Europe - Jansen, Sharon L. (Palgrave Macmillan, 2008)
Introduction: An age of queens -- Queens and controversy : John Knox and The monstrous regiment of women -- The gynecocracy debate -- The gynecocracy debate in context : humanism and history -- The gynecocracy debate : women's voices -- Queens and controversy in early modern Europe : the end of an era